A.A. ISTRI AGUNG: A MARGINALIZED WOMAN DUE TO THE DUTCH COLONIAL POLITICS - Suastika, I Made; Puspawati, Luh Putu (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
The heartbreaking story of "Mandulame" even beyond humanitarian boundaries occurred in Karangasem Castle, when the colonial government entered and intervened in determining the movement of government. The Dutch Colonial Government began to interfere in power. On behalf of Mr. Controller, Mr. Governor General at Betawi, and Ratu Koningen (queen of the Netherlands) in The Hague, the king and empress who ruled were thrown into Jembrana, precisely in the village of Cupel. Much of the suffering suffered by AA Great Wife as a consort then became an ordinary person in his captivity. Honorable people in the kingdom suddenly became poor and lacked in distress. Even her husband died in captivity at Jembrana.